Effects of octenidine mouth rinse on apoptosis and necrosis of human fibroblasts and epithelial cells – an in vitro study. (3rd April 2018) - Schmidt, J.; Zyba, V.; Jung, K.; Rinke, S.; Haak, R.; Mausberg, R.F.; Ziebolz, D.
Abstract: This study aimed at comparing the cytotoxicity of a new octenidine mouth rinse (MR) on gingival fibroblasts and epithelial cells using different established MRs. Octenidol (OCT), Chlorhexidine 0.2% (CHX), Meridol (MER), Oral B (OB), and control (PBS only) were used. Human primary gingival fibroblasts (HGFIBs) and human primary nasal epithelial cells (HNEPCs) were cultivated in cell-specific media (2 × 10 5 cells/well) and treated with a MR or PBS for 1, 5, and 15 min. All tests were performed in duplicate and repeated 12 times. The apoptosis and necrosis were determined using a Caspase-3/7 assay and LDH assay, respectively. The data were analyzed using two-way analysis of variance with subsequent Mann–Whitney U -test. No significant differences could be found between the incubation times of the MR, neither for apoptosis nor necrosis ( p > 0.05). Regarding apoptosis of HGFIBs, MRs had no influence at all. In HNEPCs, OCT induced relevantly lower apoptosis than CHX ( p = 0.01). Considering necrosis, MER showed the lowest numbers of necrotic HGFIBs and HNEPCs, whereas OB induced the highest number of necrotic cells. The differences between both MR were statistically relevant ( p < 0.01). OCT did neither differ from the other MRs nor from the control (PBS) in induction of necrosis in both cell types. In conclusion, the slightly negative effect of OCT considering apoptosis and necrosis of HGFIBs and HNEPCs is nearly the same or even lower compared to the established MRs included in this study. The results confirm that OCT is a potential alternative to CHX.